2018
DOI: 10.1590/0004-282x20180106
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Alzheimer's disease in the Brazilian population

Abstract: Dementia is a very common disease, but the general population's knowledge about its main etiology, Alzheimer's disease (AD), is still poor, leading to delayed seeking of healthcare services, less prevention of disease by lifestyle changes and more difficulty in managing the care of the demented. Objective: To measure knowledge about AD in a Brazilian sample, taking into account some demographic variables. Methods: A link to a self-administered online questionnaire was sent by email and via other social media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
1
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 31 publications
5
41
1
11
Order By: Relevance
“…Despite generally good knowledge, risk factors and prevention of AD were noteworthy gaps. Our results are consistent with previous studies 7, [22][23][24] In a systematic review of 40 studies addressing the public's knowledge of AD, Cahill et al found a poor to very limited level of AD literacy. 7 The most common correlates of knowledge investigated were age, sex, and education.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Despite generally good knowledge, risk factors and prevention of AD were noteworthy gaps. Our results are consistent with previous studies 7, [22][23][24] In a systematic review of 40 studies addressing the public's knowledge of AD, Cahill et al found a poor to very limited level of AD literacy. 7 The most common correlates of knowledge investigated were age, sex, and education.…”
Section: Discussionsupporting
confidence: 93%
“…Krempel-Amado et al found a moderate knowledge of AD in a survey including 1414 people in Brazil (mean ADKS score = 21.6). 23 The scores were positively influenced by educational level, professional skills (better for health professionals, mainly physicians) and by age (younger than 65 years). Healthcare professionals also show knowledge gaps about AD, with risk factors and disease course being the most frequent identified gaps.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The present study revealed that the overall percentage of total Alzheimer's disease knowledge score ranged between 26.7 and 100% with a mean of 58.5%, median of 60%, mode of 56.7% which indicate moderate level of knowledge. Quite similar findings were observed among general population in Brazil [14]. However, expectedly higher figures were reported in studies carried out among pharmacists in Malaysia [15], healthcare professionals in Australia [16], and psychologists in Norway [17].…”
Section: Discussionsupporting
confidence: 79%